Military Collections in the Late Empire - Shaw, Wendy (Possessors and Possessed, 2003)
In light of the auspicious beginnings of Ottoman museums in the dual collections at the Basilica of Hagia Irene, it would have been almost impossible to conceive of the construction of a modern Ottoman identity that did not make use of the prodigious military legacy of the empire in its construction of national heritage. Nonetheless, under Abdülhamid II, the weapons inside the former church were perceived as too dangerous to remain accessible to the public in any form. The museum closed and was heavily guarded.¹ The sovereign nonetheless retained an interest in the promotion of Ottoman identity through a military